2020
DOI: 10.11606/issn.2525-376x.v4i1p85-91
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da percepção de graduandos da USP referente à integração do ensino acadêmico com a tecnologia em saúde

Abstract: A demanda em integrar ensino acadêmico e as Tecnologias em Informação e Comunicação (TICs) é crescente nos dias atuais, visto que os avanços na tecnologia impactam diretamente a produção científica e estão fortemente presentes no cotidiano dos universitários. O objetivo deste trabalho foi avaliar a percepção de graduandos da área da saúde da Universidade de São Paulo, campus capital, com relação à integração entre ensino acadêmico e tecnologia, por meio de um questionário eletrônico. O questionário apresentava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…All the professors taught ROL classes during the pandemic (90% with synchronous and asynchronous activities and 10% with synchronous activities). Such results corroborate those obtained by previous study ( 14 ) , who assessed how undergraduate health students perceived the integration of academic teaching with technology. They observed that those students often use digital platforms, which make their learning and professional practice easier, and that they want to increase their knowledge continuously using technology tools while in college.…”
Section: Discussionsupporting
confidence: 91%
“…All the professors taught ROL classes during the pandemic (90% with synchronous and asynchronous activities and 10% with synchronous activities). Such results corroborate those obtained by previous study ( 14 ) , who assessed how undergraduate health students perceived the integration of academic teaching with technology. They observed that those students often use digital platforms, which make their learning and professional practice easier, and that they want to increase their knowledge continuously using technology tools while in college.…”
Section: Discussionsupporting
confidence: 91%
“…As in another study using e-learning, students show interest in improving knowledge using digital platforms since they consider that teaching-learning is facilitated when e-learning tools are applied. They agree that these tools favor the expansion of knowledge for professional practice [22].…”
Section: Discussionmentioning
confidence: 94%